The Human–Canine Bond: A Sacred Relationship. Issue 1 (2nd January 2016) - Maharaj, N.; Kazanjian, A.; Haney, C. J.
ABSTRACT: Human beings attempt to find meaning in their everyday lives. The relational significance of the human-animal bond is no exception. This article draws upon a qualitative study examining the subjective experience of living with a companion dog. Dog owners ( n  = 27) were invited to participate in focus groups. Based on a thematic analysis, three themes are highlighted: (a) this is a sacred relationship; (b) all we have is today; and (c) I'm going to fix you, hang on. Discussed in light of interdisciplinary perspectives, these findings may lead to a deeper understanding of the human-animal bond in research and clinical work.